Cherry Picking: Virginity Loss Definitions Among Gay and Straight Cisgender Men. Issue 6 (12th May 2018) - Huang, Howard
ABSTRACT: Virginity loss is a vital milestone in the development of one's sexual identity. Unfortunately, there is very little literature available studying virginity loss definitions among the wider straight population, and even less examining virginity loss among LGBTQ+ populations. The present study recruited 251 (45.4%) cisgender straight men and 114 (54.6%) cisgender gay men. An online, anonymous survey was administered to explore whether they considered various male-on-male (M-M) and male-on-female (M-F) sexual behaviors as constitutive of virginity loss. Results indicate that more gay men than straight considered M-M receptive anal intercourse (i.e., bottoming) and M-F penetrative anal intercourse to be constitutive of virginity loss. Results also indicate that both gay and straight men almost unanimously endorsed M-F penovaginal sex to be constitutive of virginity loss. This study is a first-step toward gaining a better understanding of LGBTQ+ virginity loss conceptualizations. Future research is strongly encouraged.